HUBUNGAN ASUPAN GIZI DENGAN AKTIVITAS BELAJAR SISWA SEKOLAH DASAR - Dwi Rahayu Ningsih (UNIVERSITAS SARJANAWIYATA TAMANSISWA, 2017)
The purpose of this research is to know (1) nutrient intake, (2) learning activities, and (3) nutritional intake relationship with learning activity Taman Muda (SD) Tamansiswa Sekota Yogyakarta. The research population is students and students in Taman Muda (SD) Tamansiswa Sekota Yogyakarta with 94 students. This study included sample research. Random sampling technique, ie sample taken 60% plus 10% for missing data. Thus, the sample of this study was 57 + 6 = 63. This study included the type of ex-post facto research. The data tested the validity, reliability and data analysis techniques Product Moment correlation. The results showed that there is a positive and significant relationship between the variables between nutritional intake with learning activities. The determinant coefficient (R2) is 0.310, meaning that the contribution contribution of nutritional variable to learning activity variable is 31%, while the rest 69% is influenced by other factors not discussed in this research.Â Keywords: nutritional intake, learning activity